Understanding joint bids for international large-scale sport events as strategic alliances - Byun, J.; Leopkey, B.; Ellis, D. (Sport, Business and Management, 2020)
Purpose: The purpose of this paper is to present a theoretical analysis that examines joint bids that unite multiple cities or nations in a bid for hosting international large-scale sport events from the perspective of strategic alliances. Design/methodology/approach: Using previous strategic alliance research and examples of joint sport event bids, this study discusses how joint event bids can be understood as strategic alliances. Findings: Motivations of bidders and driving forces behind the formation of joint bids are identified and analyzed. By integrating theories used in the area of strategic alliances, this study provides an agenda for moving research on joint bids forward as the practice continues to expand. Originality/value: As a conceptual paper, the findings of this study can be a starting point for future research not only on joint bids but also on inter-organizational relationships in the context of sport event bidding.